Activation cross sections of proton induced nuclear reactions on palladium up to 80 MeV. (August 2016) - Tárkányi, F.; Ditrói, F.; Takács, S.; Csikai, J.; Hermanne, A.; Uddin, M.S.; Baba, M.
Abstract: Activation cross sections of proton induced nuclear reactions on palladium were measured up to 80 MeV by using the stacked foil irradiation technique and gamma ray spectrometry. The beam intensity, the incident energy and the energy degradation were controlled by a method based on flux constancy via normalization to the excitation functions of monitor reactions measured in parallel. Excitation functions for direct and cumulative cross-sections were measured for the production of 104 m, 104 g, 105 g, 106 m, 110 m Ag, 100, 101 Pd, 99 m, 99 g, 100, 101 m, 101 g, 102 m, 102 g, 105 Rh and 103, 97 Ru radioisotopes. The cross section data were compared with the theoretical predictions of TENDL-2014 and -2015 libraries. For practical applications thick target yields were derived from the measured excitation functions. Application in the field of medical radionuclide production is shortly discussed. Highlights: Proton induced reactions on natural palladium up to 80 MeV. Stacked foil irradiation including monitor and energy degrader foils. Comparison of experimental results with the TENDL-2014 and -2015 libraries. Calculation and comparison of thick target integral yields. Discussion of application fields.